Lymphomas associated with Epstein-Barr virus infection in 2020: Results from a large, unselected case series in France. (December 2022) - Donzel, Marie; Bonjour, Maxime; Combes, Jean-Damien; Broussais, Florence; Sesques, Pierre; Traverse-Glehen, Alexandra; de Martel, Catherine
Summary: Background: Despite mounting evidence for a causal role in an increasing number of lymphoma subtypes, very few studies have systematically tested the entire spectrum of Hodgkin and non-Hodgkin lymphomas for the presence of Epstein-Barr virus (EBV). Here, we describe the prevalence of EBV in a large, unselected series of patients diagnosed with any type of lymphoma during 2020, in the pathology department of a single University Hospital in France. Methods: A total of 756 lymphoma cases (89% new diagnoses and 11% relapses), were registered in the department between Jan 1 and Sept 30, 2020 and 616 were successfully tested for EBV presence in tumour cells by EBV-encoding RNA in-situ hybridisation, using double-blinded assessment and a scoring system designed in accordance with the current state of knowledge in the literature Findings: A strong association with EBV was described in 27/87 (31%) classic Hodgkin lymphomas, 12/223 (5%) diffuse large B-cell lymphomas, and 18/71 (25%) NK and T-cell lymphomas: 4 extranodal NK/T-cell lymphomas, nasal type, 14 angioimmunoblastic T-cell lymphomas (48%). In Hodgkin and NK and T-cell lymphomas, there was a statistically significant association between EBER positivity and relapse ( p  < 0·01). Among other subtypes, a potential association with EBV (≥10% stained cells) was found in 2/97 (2%) follicular lymphomas, both of grades 1–2, 1/19 (5%) chronic lymphocytic leukaemia (CLL), 1/9 lymphoplasmacytic lymphomas (11%), and 2/47 (4%) marginal zone lymphomas. Interpretation: When applied to the distribution of lymphomas in France as described in the Lymphopath database, our data suggested that at least 8% of all combined Hodgkin and non-Hodgkin lymphomas are associated with EBV. Funding: International Agency for Research on Cancer (IARC/WHO).